Approaches and Models in the Development of Islamic Religious Education Curriculum - Evi Sulfaningsih; Nurhidayat Nurhidayat (YASIN, 2026)
Curriculum reform in Islamic Religious Education (PAI) has attracted significant scholarly attention in recent years; however, comprehensive studies that systematically integrate curriculum approaches and development models within a unified analytical framework remain limited. This study aims to analyze the dominant approaches and curriculum development models in PAI and to examine their interrelationship in responding to contemporary educational challenges. Employing a qualitative approach with a library research design, the study draws on primary and secondary academic sources related to curriculum theory and Islamic education, which were examined using an interactive content analysis process involving data reduction, categorization, and conclusion drawing. The findings indicate that four major approaches—academic subject, humanistic, social reconstruction, and technological—shape the philosophical orientation of PAI curriculum development. In addition, classical models such as those of Tyler and Taba remain structurally relevant, while contemporary models, including competency-based, integrative, and school-based curriculum development, provide adaptive and contextual frameworks for current educational needs. The study concludes that effective PAI curriculum development requires a hybrid model that integrates epistemological stability with methodological flexibility. The implications include theoretical clarification of the relationship between curriculum approaches and models, as well as practical recommendations for curriculum developers and policymakers to design adaptive, competency-oriented, and value-based PAI curricula in Indonesia.